Post-traumatic Stress Disorder and Depression during COVID-19 Pandemic among Students: Study at Universitas Negeri Semarang - Endika, Okta Mega Gres; Azam, Mahalul (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2021)
The high COVID-19 death rate has an impact on mental disorders. Based an online self-survey on mental health, found a percentage of 63%, 66% and 80% on anxiety, depression and stress, respectively. We aimed to determine factors related to students’ mental health during pandemic. A cross-sectional study was conducted yielding 407 students selected consecutively. Data was collected using a questionnaire on google form. Data were analyzed by logistic regression. The results showed that there was a significant relationship between age and stress symptoms (p= 0,038) and depression (p= 0,017), resilience with stress symptoms (p= 0,040) and depression (p0,001) sleep duration with stress symptoms (p=0,005) and social support with depression (p0,001) in student at State University of Semarang. The variable that is most strongly associated with symptoms of stress and depression is resilience. Based on this research, the government and universities must provide psychological services and interventions regularly to identify students who have mental health problems.